2004
DOI: 10.1525/maq.2004.18.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Miscommunication in Informed Consent to Research

Abstract: Biomedical ethics require that research subjects be aware that the drugs they take or procedures they undergo are designed to fulfill the conditions of the experiment and not to benefit a subject's health. This apparently straightforward distinction between research and treatment is a source of much controversy and misunderstanding. Ethicists have labeled this problem the "therapeutic misconception." This misconception and, more broadly, informed consent have been studied extensively. Nonetheless, the therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…The fact is, these issues speak to long-standing anthropological concerns regarding "misinformed consent" through either a user agreement or a signed institutional review board form (du Toit 1980;Sankar 2004;Wax 1980), the implications of using "naturally occurring" versus "elicited" communication (Dobrin 2008;Wolfson 1976), and the larger question of the general role and purpose of the "native voice" in anthropological texts (Bonilla n.d.;Trouillot 2003). Engagement with these questions in the context of digital platforms should thus not be set apart from discussions of "analog" methods and ethical concerns.…”
Section: Postscriptmentioning
confidence: 99%
“…The fact is, these issues speak to long-standing anthropological concerns regarding "misinformed consent" through either a user agreement or a signed institutional review board form (du Toit 1980;Sankar 2004;Wax 1980), the implications of using "naturally occurring" versus "elicited" communication (Dobrin 2008;Wolfson 1976), and the larger question of the general role and purpose of the "native voice" in anthropological texts (Bonilla n.d.;Trouillot 2003). Engagement with these questions in the context of digital platforms should thus not be set apart from discussions of "analog" methods and ethical concerns.…”
Section: Postscriptmentioning
confidence: 99%
“…114,115 An important motive in such research has been the perceived need to better understand processes of informed consent with the hope of improving recruitment, and retention into trials. 116 Research on participation in clinical trials of abortion differs in several important respects from research in other areas. First, participants tend to be young and are normally quite healthy.…”
Section: Participants' Experiences Of Involvement In the Trialmentioning
confidence: 99%
“…While a diffuse hope for a direct benefit of phase I trials has been found even in adolescent patients [15,24], the only patients who represent an exception regarding the therapeutic optimism bias are the elderly (patients over 65 years). Only few studies [25,26,27,28,29,30] are available on these patients, because the frequent comorbid conditions in these individuals are often incompatible with protocol eligibility requirements; however, they are numerous enough to allow us to note that elderly are similar to younger patients regarding cancer screening and cancer care, while they are clearly less willing to accept toxic treatment that could eventually prolong their survival but may affect their quality of life [31].…”
Section: Role Of Optimism Bias With Regard To Participating In Phase mentioning
confidence: 99%